Analysis of Residents' Participation in The Maintenance Of Public Facilities and Utilities in The Wiranda Asri Residential Area, Stabat District - Doyandri Hasibuan; Abdi Sugiarto; Cut Nuraini (CV. Doki Course and Training, 2026)
This study aims to analyze the level of citizen participation in the maintenance of public facilities and utilities in the Wiranda Asri Housing Complex, Stabat District. The research method used is descriptive qualitative with data collection techniques through observation, interviews, and documentation. The results show that citizen participation is present in various forms, namely labor participation (mutual cooperation), financial (contributions), ideas (deliberations), and socio-security (night watch). However, the intensity of participation among residents is uneven. Facilities such as neighborhood roads and prayer rooms are well maintained due to regular financial and labor support, while drainage and green open spaces are less supervised. Factors driving participation include awareness of direct benefits, a sense of ownership, and a culture of mutual cooperation. Inhibiting factors include limited time, lack of transparency of funds, minimal communication, and differences in social status and home ownership. This study recommends strategies to increase participation through strengthening communication systems, transparency of fund management, alternative participation schemes, and the formation of environmental management teams. With a more structured approach, citizen participation can become the foundation for sustainable management of public facilities in the housing complex.